Model Konsep Teori Keperawatan Hildegard Elizabeth Peplau pada Celulitis Ante Brachii Osteomielitis dan DM II - Kurniati Kurniati; Irna Nursanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the application of Hildegard E. Peplau's Nursing Model Theory in the nursing care of patients with Cellulitis Ante Brachii Osteomyelitis and Diabetes II, where patients experience not only anxiety but also other physical problems such as pain and unstable blood sugar levels. The research method used a qualitative approach by conducting case studies on patients. The results showed that nurses who apply Peplau's theory by implementing therapeutic communication in building interpersonal relationships with patients can overcome anxiety and physical problems experienced by patients. Nurses and patients develop emotionally through four stages of the relationship: orientation, identification, exploitation, and termination. Each stage describes a mutually reinforcing and flexible relationship with intervention options tailored to SIKI and SLKI. In conclusion, this contributes to the development of understanding of the application of Peplau's theory in nursing care, which not only focuses on emotional issues such as anxiety but can also be modified to address other physical and health problems holistically. Keywords: Hildegard Peplau, Interpersonal Relationships, Nursing Theory